Competition When Consumers Value Firm Scope - Nathan H. Miller (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2008)
I model multimarket competition when consumers value firm scope across markets. Such competition is surprisingly common – consumers in many industries prefer firms that operate in more geographic and/or product markets. I show that these preferences permit firms of differing scopes to coexist in equilibrium. Within markets, firms of greater scope have higher prices and market shares. I turn to the commercial banking industry for the empirical implementation. Structural estimation of the model firmly supports the assumptions on consumer preferences, and empirical predictions specific to the model hold in the data. The results suggest that theoretical model is empirically relevant.
Keywords: G21; L11; L22; 330; Firm Scope; Consumer Preferences; Multimarket Competition; Banks